Development of Literacy-Numeracy Adaptive Test Application: A Case Study of the Al-Ashirriyah Nurul Iman Foundation, Indonesia - Sutisna, Anan; Badrujaman, Aip; ., Soeharno; Ningtyas, Lisa Dwi; Afriadi, Bambang (Journal of Cultural Analysis and Social Change, 2025)
This study aims to develop an application of adaptive literacy-numeracy tests at the Al-Ashirriyah Nurul Iman Foundation, Bogor, Indonesia, with a focus on improving the quality of assessment and the efficiency of learning evaluation. The application developed integrates a Computerized Adaptive Testing (CAT) system based on Item Response Theory (IRT) to adjust the difficulty of questions to students' abilities dynamically. The approach used is research and development (R&D) with testing of application prototypes through trials to students and teachers. The results show that this application can reduce evaluation time by up to 40% and provide more accurate assessments than conventional test methods. In addition, this application can provide faster, more relevant feedback to students and make it easier for teachers to analyze test results. Based on the research results, it is recommended to further develop this application by expanding its features and improving teacher training in the use of technology to support more effective technology-based learning.